Mito e storia sacra nella Parhenice prima sive Mariana di Battiststa Spagnioli - Górka, Elżbieta (Polskie Towarzystwo Filologiczne, 2022)
The article provides an analysis of the ways in which myth and Christian themes intertwine within the biblical epic Parthenice Mariana by the Italian Carmelite Baptista Spagnoli (1447–1516). The poet, following the example of the ancient bee, skilfully selects images and motifs drawn from classical mythology and Roman legendary past that – usually after appropriate transformation – can be adapted for a biblical epic. Following the humanistic postulate of imitatio antiquorum, the poet inlays his poem with mythological ornamentation and makes use of analogical motifs rooted in both pagan and Christian traditions. Competing with the ancient tradition (aemulatio antiquorum), he emphasises the moral superiority of Christianity over the illusory realm of ancient religion.